Investigation of Synthetic Musks Fragrances Pollutants in Human Breast Milk - Yakout1, S.M.; M. Isa3, Ahmed (Asian Journal of Chemistry, 2014)
Synthetic musks, including nitro musks and polycyclic musks are widely used in a variety of personal care and cleaning products as fragrance ingredients. Synthetic musks have been reported to be ubiquitously present in the environment and can accumulate in animal and human tissues owing to their lipophilic nature. Recently, as a result of the potential toxicity of synthetic musks observed in both in vivo and in vitro studies, human exposure to these compounds has been a great concern. Synthetic musks are detected in human maternal blood, breast milk and adipose tissue samples. Human milk is extensively used for identifying and monitoring the body burden of lipophilic and persistent environmental pollutants due to great samples volumes can be collected non-invasively compared with blood and adipose tissue. Additionally, the concentrations of organic pollutants in human milk can reflect the exposure levels of breastfed infants, as well as the contamination status of the local environment. A lot of information already exists on regulated contaminants and human health. but there is less information on the influence of the synthetic musks fragrances on human. For this reason it is presume that this work is timely due to increased interest in the last years to bridge human health with environmental contamination especially synthetic musks. The establishment of relationships between human health and levels of some of these emerging contaminants in human milk is taking place at global scale.